2010
DOI: 10.2174/1874941001003010117
|View full text |Cite
|
Sign up to set email alerts
|

Compulsory Commitment to Care of Substance Misusers – A Worldwide Comparative Analysis of the Legislation~!2009-12-02~!2010-06-14~!2010-07-23~!

Abstract: This study explores the worldwide use of compulsory commitment to care (CCC) at the end of the 20 th century and evaluates the implementation of WHO recommendations since the 1960s. Based on three WHO reports, the legislation of 90 countries and territories are analyzed, and types as well as predictors of such legislation are analyzed in multivariate models from country characteristics. Laws on CCC for alcohol and drug misusers are common all over the world; more than 80 percent of the countries and territorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 20 publications
0
23
1
Order By: Relevance
“…Legislation on CCC in Europe did not differ from the international picture [19] . Of the 30 European countries included, 25 countries (83%) had legislation on compulsory care or compulsory placement in treatment of substance misusers.…”
Section: International Legislative Outlookmentioning
confidence: 71%
See 1 more Smart Citation
“…Legislation on CCC in Europe did not differ from the international picture [19] . Of the 30 European countries included, 25 countries (83%) had legislation on compulsory care or compulsory placement in treatment of substance misusers.…”
Section: International Legislative Outlookmentioning
confidence: 71%
“…A comparative study [19] , based on three WHO reports [17,18,20] , reported that 82% of 90 countries and territories had active laws on CCC for substance misusers. The sheer existence of laws on CCC was not related to country characteristics, but the type of such laws was.…”
Section: International Legislative Outlookmentioning
confidence: 99%
“…All reported law on CCC. Israelsson and Gerdner [4] combined these data for 90 countries. Within criminal justice legislation, only those laws mandating through court orders were counted, not laws that concerned diversion to treatment with full consent including possibility to withdraw.…”
Section: Introductionmentioning
confidence: 99%
“…Within criminal justice legislation, only those laws mandating through court orders were counted, not laws that concerned diversion to treatment with full consent including possibility to withdraw. With these added to compulsory civil commitment, Israelsson and Gerdner [4] concluded that 82% of the 90 countries had some law on CCC at the eve of the 20th century. In a more recent study on 38 European countries, Israelsson [5] found that 74% had some such law.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation